PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN QUIZIZZ TERHADAP HASIL BELAJAR MAHASISWA MATA KULIAH ANALISA DAN DESAIN SISTEM INFORMASI - Yuliana, Dyan; Baijuri, Achmad; Suparto, Arico Ayani; Seituni, Siti; Selvianda, Niken Pundri (UIN Ar-Raniry, 2024)
The development of Information and Communication Technology is currently growing very rapidly, this is proven by the emergence of sophisticated technological equipment that has changed human lifestyles today. As educators, of course we must be able to adapt the way we educate them according to the current lifestyle in the digital era in order to prepare them to face challenges in the future. Educators are required to make innovations in the learning process. To support the needs needed to implement active learning in the classroom, there needs to be media that can support the implementation of learning optimally to stimulate effective communication skills through active learning that integrates information and communication technology. One of the learning media that is widely used today is Quizizz, which is an educational game application that can support the learning process significantly for measuring or assessing the learning process. Presenting questions in game form can attract students' interest, so that they will be more enthusiastic in working on the questions given. This research uses a quantitative research approach with a pre-experimental design type with a one group pretest posttest design research form. Decision making through hypothesis testing using the SPSS version 29 application. The hypothesis testing technique uses the paired sample t-test and simple linear regression test. The results obtained from the paired sample t-test in SPSS version 29 are known as the sig value. (2-tailed) of 0.001. In accordance with the basis for decision making in the paired sample T-test that the sig. (2-tailed) < 0.05 or 0.001 < 0.05, then H0 is rejected and Ha is accepted, meaning that there is a significant difference between the pretest and posttest results with an influence level of 0.144 or 14.4% so it can be concluded that there is an influence of use Quizizz learning media on the learning outcomes of fifth semester students in the Information Systems Analysis and Design course at STKIP PGRI Situbondo.